Conoscenza tacita e conoscenza esplicitata. Una ricerca cognitivista - Federica Biondi (Quaderni di Sociologia, 2008)
The essay reports on a research inspired about a concept of tacit knowledge — valued in the second half of ’900 by Michael Polanyi — and, most in general, about the relationship between thought and language. The goal is about to show empirically the lack relationship between the two elements. Thought is not a tangible element if not by language. Anyway by language it is not possible to produce perfectly our thought.For this reason I emphasized the point that common man has not got a clear and unique idea not even about the most elementary objects (as a chair, as lamp or a lie.) in ordinary life. Defining a meaning who should be refer to a specific concept, people are not able to explicit all the typical elements about the intention of a concept, although people are able to delimit the extention of the concept itself.Through my analysis a few doubts have rised about cartesianan thesis in a clear and unique nature of human knowledge. Furthermore my analysis give me the chance to note the difference between people in a term definitions. Besides terminologics misunderstanding between interviewers and respondents are a classic theme of a methodological research. Lazarsfeld had already underlined the lack of attention to the compiling of questions and pre-codified answers, even so the standard questionnaire has based on a perfect condivision of an usual terms meaning between researchers, interviewers and respondents. By the fact that my respondents are not scientific researchers, the importance of this results for a science vision it is only an indirect matter. Eventought that full continuity between common knowledge and a scientific one is a thesis very supported in epistemological matter — by Schutz to Garfinkel, by Cicourel to the School of Edimburourgh, by Latour until Morin — it should be unjustified to give them irrelevant meaning.